Antimicrobial susceptibility of Porphyromonas spp. isolated from dogs with periodontal disease in South Korea - Kim, Taesoo; Choi, Yi-Don; Hur, Won; Lee, Sang-Won; La, Tae-Min (Frontiers in Veterinary Science, 2025)
Porphyromonas spp. are oral anaerobes that play a key role in the pathogenesis of canine periodontal disease. Despite their clinical relevance in veterinary medicine, data on the antimicrobial susceptibility of canine Porphyromonas isolates remain limited. Therefore, we assessed the antimicrobial susceptibility of Porphyromonas spp. isolated from the subgingival plaque of dogs with periodontitis in South Korea. Fifty-eight dogs diagnosed with periodontal disease were screened for Porphyromonas spp., and species identification was confirmed using PCR and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry. Antimicrobial susceptibility testing was performed using the broth microdilution method with the Sensititre AN02B panel. Overall, 40 isolates were recovered from 30 of the 58 dogs sampled, comprising 15 Porphyromonas gulae, 11 Porphyromonas macacae, eight Porphyromonas gingivalis, five Porphyromonas gingivicanis, and one Porphyromonas crevioricanis. Resistance was detected in six isolates (15%) to penicillin, three (7.5%) to imipenem, three (7.5%) to meropenem, 15 (25%) to clindamycin, and seven (17.5%) to ampicillin. No resistance was observed to ampicillin/sulbactam, amoxicillin/clavulanic acid, cefotetan, cefoxitin, metronidazole, chloramphenicol, piperacillin, tetracycline, mezlocillin, or piperacillin/tazobactam. These findings provide crucial insights into the antimicrobial susceptibility patterns of canine oral Porphyromonas spp. and highlight the importance of judicious antimicrobial use in veterinary dentistry.